2000
DOI: 10.1557/proc-663-35
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characteristics of a New Porous Glass Crystalline Matrix (Gubka) for Stabilizing Radioactive and Hazardous Solutions

Abstract: This paper describes the results of a joint research program of Russian institutes at St. Petersburg, Krasnoyarsk and Zheleznogorsk and the Idaho National Engineering and Environmental Laboratory to develop a new material for stabilizing radioactive solutions and other uses, such as high-temperature catalysis. An open-cell glass crystalline porous material, Gubka, or “sponge” in Russian, having an open-cell porosity of up to 90 %, was produced from hollow glass crystalline microspheres (cenospheres) formed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[15] The material is an open-cell glass crystalline porous material, shown in Fig. 1, that is produced from hollow glass crystalline microspheres (cenospheres) formed as small mineral slag particles in fly ash from coal combustion.…”
Section: Synthesis Of Amp-cenospheresmentioning
confidence: 99%
“…[15] The material is an open-cell glass crystalline porous material, shown in Fig. 1, that is produced from hollow glass crystalline microspheres (cenospheres) formed as small mineral slag particles in fly ash from coal combustion.…”
Section: Synthesis Of Amp-cenospheresmentioning
confidence: 99%
“…The porous matrices were successfully tested at radiochemical plants in Russia and United States in different variants of the immobilization of liquid radioactive wastes, including the solidification with fixation of radionuclides in a free volume of the matrix with the aim of transporting to sites of storage or further repro- cessing [25,26]. It was demonstrated that the saturation of the porous matrices after calcination is as high as 45 wt % with respect to nitrates and 33 wt % with respect to oxides.…”
Section: Porous Matrices Intended For Conditioning Liquid Radioactivementioning
confidence: 99%
“…Porous matrices were saturated to 55 wt % with nitrate salts, and calcinated products were saturated to 33 wt % with oxides [24][25][26]. These experiments showed that porous matrices based on coal fly ash cenospheres can be used for intermediate storage of solidified radioactive wastes and transportation to sites of reprocessing or long-term storage.…”
Section: Use Of Porous Matrices Based On Coal Fly Ash Cenospheres Formentioning
confidence: 99%